Uji Kinerja Panel Surya Monocrystalline Terhadap Baterai Valve Regulated Lead ACID - Galman Marcelino Pudi; Audy Fryan Agow; Jedithjah Naapia Tamedi Papia (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
This study aims to determine (1) the power released from monocrytalline solar panels to VRLA battery types (charging process); (2) the power that comes out of the VRLA battery used by the water pump (discharging process). This research uses experimental methods, and uses a type of quantitative research. Based on the results and discussion, it can be concluded as follows: (1) the highest intensity of sunlight 158400 Lux occurred in the first test, time 11.10, temperature 32.6 oC, electric voltage 11.59 V, electric current 4.65 A, mains power 53.7 W, Watt Hour 31.5 Wh; the lowest intensity of sunlight 65300 Lux occurred at 10.30, temperature 32.5 oC, electric voltage 11.72 V, electric current 1.8 A, electric power 21 W, power at 16.3 Wh; (2) an increase in the intensity of sunlight on a solar panel results in an increase in the power generated, conversely a decrease in the intensity of sunlight in a solar panel results in a decrease in the power generated; (3) the power that comes out of the VRLA battery and is used by the water pump is an average of 102.94 W.